Avaliação da ventilação e insolação em edificações na região de Bauru - SP - Donida, Mônica Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
O objetivo principal deste trabalho foi o de analisar algumas edificações de abrigos animais e destinadas à habitação popular, tanto no meio rural como no urbano, existentes na região de Bauru – SP, e apresentar sugestões arquitetônicas que sejam tecnicamente viáveis e de baixo custo, de forma a melhorá-las em termos de conforto térmico. Para isso, foi realizado um breve histórico sobre o panorama destas edificações e seu sistema de ventilação e insolação, objetivando torná-las mais confortáveis. Foram propostos, também, dispositivos de proteção solar capazes de reduzir a carga térmica incidente sobre as mesmas bem como o direcionamento do fluxo da ventilação.

The chief purpose of this study is to analyze some animal shelter structures and the ones designed for public housing, both in the rural and urban areas situated in the region of Bauru – SP. It is also intended to present feasible technical and economic architectonic suggestions with the aim of enhancing their thermal comfort. For this reason a brief report about these structures was carried out and their ventilation and insulation system with view to make them more comfortable. Solar protection devices capable of reducing the heat load, which falls upon them, and the ventilation flux direction, were also presented. Considering the comfort rate differences for each user, anent climatic, human and architectonic variable, to adjust the thermo regulator of each user. Therefore solutions were proposed to be employed in a simple way, that is, without high-qualified manual work, with available resources to make these solutions both economically and technically feasible for the existing structures.
Keywords: Habitação popular; Construções rurais; Conforto termico